Our kitchen treasures! [title page] - Hudson Bay Park Baptist Womens' Missionary Society (Electronic version published by Vancouver Island University, 1974)
Kitchen hints, weights measurements & substitutions, beverages, breads & buns, supper dishes, meat dishes & casseroles, Oriental dishes, salads & vegetables, cakes, squares, cookies frosting & candy, preserves. From the Lillian Carefoot Cookbook Collection